High-speed and high-responsivity InP-based uni-traveling-carrier photodiodes - Meng, Qianqian (2018)
In this paper, top-illuminated InP-based uni-traveling-carrier photodiodes (UTC-PDs) with dipole-doped structure which achieve both high speed and high responsivity simultaneously have been reported. With optimization of device size and layer structure, dipole-doped UTC-PDs have demonstrated a measured optical-to-electrical 3-dB bandwidth of over 40 GHz and a maximum responsivity of 0.6 A/W at optical input power of 100 mW. By using a semi-analytical equivalent circuit model, the 3-dB bandwidth was predicted to be 103 GHz. This high 3-dB bandwidth and responsivity yield a high figure-of-merit value of 61.8 A/W·GHz.